PENGARUH MODEL PBL TERHADAP HASIL BELAJAR IPA SISWA KELAS VII SMP MUHAMMADIYAH 2 MLATI - Agnes Budi; Hidayati Hidayati; Tias Ernawati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2015)
This research descriptively aimed to know the tendency of science student achievement of 7th grade students of SMP Muhammadiyah 2 Mlati Sleman which was taught by using Problem Based Learning (PBL) and Direct Instruction model. This research comparatively aimed to know the difference of science achievement between the students which was taught by using PBL model and Direct Instruction model. The type of this research is Quasi Experiment. Data analysis used t-test by analysis requirement i.e. normality test by using chi-square formulation and homogeneity test by using F-test. The result of research descriptively shows the tendency of science achievement of 7th grade students of SMP Muhammadiyah 2 Mlati Sleman which was taught by using PBL model is classified in very high category, whereas using direct instruction is classified in medium category. The result of t-test analysis shows there is very significant difference between PBL model and direct instruction model. It means there is an influence of PBL model towards science achievement. Â